Effect of Isometric Exercise on Pain in Diabetic Patients and its correlation with HBA1c - Jain, Rajshri; Chobisa, Chitrakshi A.; Khan, Jafar; Sharma, Hina; Warhade, Veenodini; Patira, Nilesh; Lohar, Deepak; Pal, Renuka; Shah, Yash; Ansari, Adil Raza (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus (DM) is a chronic condition associated with multiple complications, including generalized body pain. Isometric exercises have been proposed as a simple and effective method for pain reduction in such individuals. Objective: To analyze the effect of isometric exercise on pain in diabetic patients. Methodology: A total of 30 diabetic patients with generalized body ache were enrolled. Pain intensity was measured using the Visual Analogue Scale (VAS) before and after a 4-week isometric exercise intervention. Results: A significant reduction in pain scores was observed post-intervention. Conclusion: Isometric exercise is effective in reducing pain in diabetic individuals and can be recommended as a non-pharmacological strategy for pain management.